ANALISIS TINGKAT KESEHATAN BANK SYARIAH MANDIRI PERIODE 2011-2013 DALAM PERSPEKTIF RASIO CAMELS - Muttaqin, Muh. Syaukin (El-Qist: Journal of Islamic Economics and Business (JIEB), 2015)
This study aims to measure the health of commercial banks based on Islamic principles by using CAMELS ratio. Contributions from the application of the CAMELS ratio against the Bank Syariah Mandiri in order to assess the factors Capital, Assets, Management, Profitability, Liquidity and Sensitivity. If Bank Syariah Mandiri attention to the ratio of C (Capital) maintain and anticipate emerging risks. Additionally, using the ratio of A (Asset) anticipate the risk of default of the financing provided. The ratio of M (Management) to manage and run the business in accordance with the principles of risk management and capital adequacy of the precautionary principle. The ratio E (Earnings) address the problem of losses, raising capital in creating a profit during a predetermined period and can control the operating expenses to operating income. Then, the ratio L (Liquidity) keeping and maintaining a sufficient level of liquidity, and the latter ratio S (Sensitivity) made into a very low market risk and market risk management is carried out effectively and consistently. In this case, the study of Bank Syariah Mandiri period 2011-2013 using CAMELS ratio obtains a good picture of the plight, healthy or not healthy cycle of Bank Syariah Mandiri or financial position of the Bank Syariah Mandiri. Researcher expects that Bank Syariah Mandiri can predict bankruptcy and financial benefit ratio test in predicting a good profit in the period 2011-2013 and the future.